A pandemic affair? Digital party conferences in Spain - Mompó, Adrià; Barberà, Oscar (Frontiers in Political Science, 2025)
The COVID-19 pandemic forced parties to face a critical dilemma between freezing their internal processes indefinitely or adapting themselves to sometimes unexplored online formats. Amongst the most affected activities were party congresses. This paper contributes to the scholar debate on critical junctures and party reform, examining how changes on the environment can drive parties to transform their organisational practices and innovate on their decision-making. Our aim is two-fold: first, to explore to what extent the Covid pandemic constituted a critical juncture facilitating the digital transformation of the Spanish party conferences; second, to assess the challenges and problems faced by the different parties that held digital party conferences by 2020. Conducting a comparative case study, we examine Spanish parties’ strategies of adaptation to the lockdown and compare three online congresses celebrated in Spain during 2020. Our findings suggest that the Covid exerted an external stimulus that fostered digital innovation, although mostly among new parties. Further, internal crisis and change of leadership might have encouraged these conferences to pursue higher levels of inclusiveness and deliberation. However, parties seem to have abandoned these innovations after the pandemic, retreating to more established practices once the crisis was over.